Two new species of sea cucumbers (Echinodermata: Holothuroidea) from the seagrass meadow of Penang, Malaysia - Teoh, Vincent Yong Jian; Woo, Sau Pinn (Zootaxa, 2022)
Two new species of sea cucumber, Euthyonidiella zulfigaris sp. nov. and Acaudina spinifera sp. nov. were described. The specimens were collected from the seagrass meadow of Pulau Gazumbo and Middle Bank, located east of Penang Island, Malaysia. E. zulfigaris sp. nov. can be distinguished from its congeners based on the presence of table ossicles with round disc, spires formed with four pillars, and absence of modified support tables in tube feet. A. spinifera sp. nov. can be distinguished from its congeners based on the presence of spinose doughnut-shaped ossicles in the body wall.